Penyalahgunaan Bantuan PKH: Motif dan Dampak (Studi Kasus di Gampong Bluka Teubai Kecamatan Dewantara Kabupaten Aceh Utara). - Zulkifli; Suadi; Alwi (Jurnal Sosiologi Agama Indonesia (JSAI), 2021)
PKH has provided benefits for recipients, but its implementation in various regions does not always run well. From the beneficiary's perspective, the problem often occurs is the misuse of the assistance provided. This article briefly describes the impact and motives for the misuse of PKH assistance by beneficiary families in Gampong Bluka Teubai, North Aceh. The research method used is qualitative with a descriptive approach. Data collection techniques used are observation, interviews, and the study of relevant documents. This study found that most KPM informants used aid funds that were not following their designation. The motive for this misuse is the weak economic condition of the KPM and the assumption that the aid funds are fully proprietary so that they can be used as needed. The misuse of these aids indirectly affects the education and health aspects of KPM so that there are still KPMs who drop out of school are malnourished and stunted.